1956
DOI: 10.2307/3894236
|View full text |Cite
|
Sign up to set email alerts
|

The Apparent Digestibility of Lignin by Mule Deer

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1956
1956
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…ADL digestibilities have been reported in domestic [Faichney and Jung, 1983;Merchen, 1988] as well as in wild ruminants, e.g., deer (Odocoileus spp.) [Smith et al, 1956], European bison (Bison bonasus) [Drozdz et al, 1975], moose (Alces alces) [Schwartz et al, 1985], and okapi (Okapia johnstoni) [Crissey et al, 2000]. Despite improved analytical techniques, high digestibility coefficients for lignin continue to be reported [Faichney and Jung, 1983], and the incomplete recovery of lignin results in digestibility estimates that are too low [Faichney and Jung, 1983].…”
Section: Digestibility Studymentioning
confidence: 99%
“…ADL digestibilities have been reported in domestic [Faichney and Jung, 1983;Merchen, 1988] as well as in wild ruminants, e.g., deer (Odocoileus spp.) [Smith et al, 1956], European bison (Bison bonasus) [Drozdz et al, 1975], moose (Alces alces) [Schwartz et al, 1985], and okapi (Okapia johnstoni) [Crissey et al, 2000]. Despite improved analytical techniques, high digestibility coefficients for lignin continue to be reported [Faichney and Jung, 1983], and the incomplete recovery of lignin results in digestibility estimates that are too low [Faichney and Jung, 1983].…”
Section: Digestibility Studymentioning
confidence: 99%
“…Perhaps the lignin content of woody browses differs structurally from that found in domestic forages or perhaps deer do differ from domestic animals in their limited abilities to utilize lignin. It is interesting to note that Smith et al (1956), working with mule deer in Utah, determined that the digestibility of lignin in 9 forage species varied between 5.8 and 32%. However, these authors believed that the lignin digestion data might be attributed to inconsistencies in the lignin analysis procedure.…”
Section: The Cellulose Assay Techniques Of Salsbury Et Al (1956) Andmentioning
confidence: 99%
“…Lignin is essentially nondigestible by most domestic animals. However, Utah studies have shown that deer are able to digest up to 42 percent of this constituent in birchleaf mahogany (Cercolcarpus montanus) (Smith, et al, 1956).…”
mentioning
confidence: 99%